2018
DOI: 10.1007/s12250-018-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-hepatitis B Virus Activity of 2′,3′-Dideoxyguanosine

Abstract: 2 0 ,3 0-dideoxyguanosine (DoG) has been demonstrated to inhibit duck hepatitis B virus (DHBV) replication in vivo in a duck model of HBV infection. In the current study, the in vitro antiviral effects of DoG on human and animal hepadnaviruses were investigated. Our results showed that DoG effectively inhibited HBV, DHBV, and woodchuck hepatitis virus (WHV) replication in hepatocyte-derived cells in a dose-dependent manner, with 50% effective concentrations (EC 50) of 0.3 ± 0.05, 6.82 ± 0.25, and 23.0 ± 1.5 lm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Then they were respectively loaded onD101, DM301, X-5 and AB-8 resins. Next, they were eluted with distilled water 25%, 50% and 75% ethanol and the eluent were collected for anti-HSV-1 experiments [16].…”
Section: Antiviral Experimentsmentioning
confidence: 99%
“…Then they were respectively loaded onD101, DM301, X-5 and AB-8 resins. Next, they were eluted with distilled water 25%, 50% and 75% ethanol and the eluent were collected for anti-HSV-1 experiments [16].…”
Section: Antiviral Experimentsmentioning
confidence: 99%
“…[24,25] However, prolonged administration of the nucleoside drugs may result in the evolution of drug-resistant mutants of hepatitis B virus. [24][25][26][27] Various research groups have reported the frequency of HBV drug resistance-associated mutations (RAM) from different populations across the world based on public sequence databases. [28] Thus, there is a continuing need to develop wide range of nucleoside analogues with increased therapeutic indices and drug resistant barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 2′,3′‐dideoxyguanosine ( 8 ) exhibited potent antiviral effects on human and animal hepadnaviruses and found to be highly effective against 3‐TC and adefovir resistant mutants (Figure 1). [24] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations